The Impact of Gross Enrollment Ratio (GER) of Tertiary Education in Indonesia on the Literacy and Inclusion Index: A Case Study Of Islamic Finance in Indonesia - Zulfikar Hasan; Saifunnajar Saifunnajar (UIN Siber Syekh Nurjati Cirebon, 2021)
The inclusion and literacy of Islamic finance is an index that can use as a guide in assessing whether people living in a country know about Islamic finance. Multiple variables can conclude whether a nation knows Islamic banking, one of the variables that can use as guidelines are the literacy and inclusion index published by affiliated organisations such as the Financial Services Authority (OJK). The Financial Services Authority does a survey that can use as further research on the knowledge of the Indonesian people about Islamic Banking. Overall, the third National Financial Literacy Survey (SNLIK) conducted by the Financial Services Authority (OJK) this year showed that the financial literacy index reached 38.03%, and the financial inclusion index 76.19%. This figure improved related to the results of the 2016 OJK survey, correctly the financial literacy index 29.7% and the financial inclusion index 67.8%. Based on regional levels, for urban financial literacy index reached 41.41% and economic inclusion of urban areas amounted to 83.60%. In comparison, the literacy index and financial inclusion of rural communities were 34.53% and 68.49%. The survey results also showed that based on gender literacy index and economic inclusion of men were 39.94% and 77.24%, relatively higher than women at 36.13% and 75.15%. OJK will use the results of the 2019 financial literacy survey to refine the national financial literacy development strategy that is more effective and targeted.